Mechanistic Study of Visible-Light-Induced Photodegradation of 4-Chlorophenol by TiO2−xNx with Low Nitrogen Concentration - Guangfeng Shang; Hongbo Fu; Shaogui Yang; Tongguang Xu (International Journal of Photoenergy)
TiO2−x Nx powders with low N-doping concentrations (0.021<𝑥<0.049) were prepared by annealing commercial TiO2 (P-25) under an NH3 flow at 550°C. Regardless of UV or visible case, the photoactivities of the samples decreased as x increased, and TiO1.979N0.021 showed the highest activity for the 4-chlorophenol (4-CP) decomposition under the visible-light irradiation. The visible-light response for N-doped TiO2 could arise from an N-induced midgap level, formed above the valence band (O 2p). Electron spin resonance (ESR) measurements and the radical scavenger technologies gave the combined evidence that the active species (•OH and O2•−) are responsible for the photodecomposition of 4-CP over TiO2−xNx under the visible irradiation. A possible photocatalytic mechanism was discussed in detail.